2011
DOI: 10.1016/j.ejvs.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Free Tissue Transfer in the Management of Non-traumatic Lower Extremity Wounds in Patients with Diabetes

Abstract: In conclusion free tissue transfer achieves successful wound healing in selected patients with diabetes and difficult to heal wounds that would have required amputation. Pre-operative optimisation of vascular supply and eradication of infection is key to success. Objective wound assessment scores and a clear multidisciplinary team (MDT) approach would improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…39,40 Some authors report the use of NPWT will reduce the frequency of debridement required in diabetic foot wounds, and its application is unlikely to reduce the efficacy of topical antibiotics in a preclinical animal model. 41 Assessment and input by the plastic surgeons is sought early. Where required, lower limb revascularization is prioritized to treat the peripheral arterial disease.…”
Section: Local Antibiotic Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Some authors report the use of NPWT will reduce the frequency of debridement required in diabetic foot wounds, and its application is unlikely to reduce the efficacy of topical antibiotics in a preclinical animal model. 41 Assessment and input by the plastic surgeons is sought early. Where required, lower limb revascularization is prioritized to treat the peripheral arterial disease.…”
Section: Local Antibiotic Loadingmentioning
confidence: 99%
“…Thereafter, skin grafting, or a similar form of plastic surgical procedure, may be performed to achieve soft tissue coverage of the wound, and follow the reconstructive ladder. 41 Residual bony instability or deformity can be managed with a brace or surgical stabilisation. A second stage of definitive fixation may be performed at this time point.…”
Section: Local Antibiotic Loadingmentioning
confidence: 99%
“…However, as microsurgical skills have developed, free tissue transfer can now allow extensive amputation to be avoided. [ 21 ] Removing bones with osteomyelitis is unavoidable, [ 22 ] but free tissue transfer can save soft tissue as much as possible. As a result, the length of the extremity can be preserved to the greatest extent possible.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, for some procedures, such as tissue grafting, ensuring an uninfected surgical field is crucial. One systematic review of 18 studies of lower extremity wounds in diabetic patients identified infection as the main cause for early flap loss [40]. In non-infected flaps, lack of healing was associated with anastomotic failures, local thromboses, stress on the graft edges, or arteriopathy [40].…”
Section: Surgical Reconstructionmentioning
confidence: 99%